The problem derived from recognizing the effects of gestation contract subrogated from the perspective of labor law and social security - Tomás Mataix, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The surrogate motherhood contract is declared invalid in Spain because it is clearly contrary to the most essential principles of our legal system, this being expressed by the Law 14/2016, 26th of May. However, a series of effects derive from the celebration in the field of Labor and Social Security Law, arising from the creation of a new family reality resulting from the birth of a minor.
Keywords: surrogate motherhood; nullity; social security; social rights; children´s interest